On the relevance of the metadata used in the semantic segmentation of indoor image spaces - Vasquez-Espinoza L. (2021)
This work has been partially funded by the Spanish Ministry of Sci-ence, Education and Universities, the European Regional DevelopmentFund and the State Research Agency [grant number RTI2018-098156-B-C52], and by FONDECYT / World Bank [grant number 026-2019FONDECYT-BM-INC.INV].